Understanding tobacco industry pricing strategy and whether it undermines tobacco tax policy: the example of the UK cigarette market. (16th April 2013) - Gilmore, Anna B.; Tavakoly, Behrooz; Taylor, Gordon; Reed, Howard
Abstract Aims Tobacco tax increases are the most effective means of reducing tobacco use and inequalities in smoking, but effectiveness depends on transnational tobacco company (TTC) pricing strategies, specifically whether TTCs overshift tax increases (increase prices on top of the tax increase) or undershift the taxes (absorb the tax increases so they are not passed onto consumers), about which little is known. Design Review of literature on brand segmentation. Analysis of 1999–2009 data to explore the extent to which tax increases are shifted to consumers, if this differs by brand segment and whether cigarette price indices accurately reflect cigarette prices. Setting UK. Participants UK smokers. Measurements Real cigarette prices, volumes and net‐of‐tax‐ revenue by price segment. Findings TTCs categorise brands into four price segments: premium, economy, mid and 'ultra‐low price' (ULP). TTCs have sold ULP brands since 2006; since then, their real price has remained virtually static and market share doubled. The price gap between premium and ULP brands is increasing because the industry differentially shifts tax increases between brand segments; while, on average, taxes are overshifted, taxes on ULP brands are not always fully passed onto consumers (being absorbed at the point each year when tobacco taxes increase). Price indices reflect the price of premium brands only and fail to detect these problems. Conclusions Industry‐initiated cigarette price changes in the UK appear timed to accentuate the price gap between premium and ULP brands. Increasing the prices of more expensive cigarettes on top of tobacco tax increases should benefit public health, but the growing price gap enables smokers to downtrade to cheaper tobacco products and may explain smoking‐related inequalities. Governments must monitor cigarette prices by price segment and consider industry pricing strategies in setting tobacco tax policies.